2016
DOI: 10.2527/jas.2016-0540
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the effects of selection on French Large White reproductive performance using frozen semen

Abstract: Genetic trends for male and female sexual development and components of litter size and weight at birth (LB) as well as traits related to sow lifetime productivity were estimated in a French Large White (LW) pig population using frozen semen. Two experimental groups (EXP = L77 and L98) were produced by inseminating LW sows with either stored frozen semen from 17 LW boars born in 1977 (EXP = L77) or with semen from 23 LW boars born in 1998 (EXP = L98). In each group, about 100 males were measured for testicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
6
0
5
Order By: Relevance
“…In polytocous livestock species, litter size is studied in order to increase prolificacy, which is the result of complex interactions between male, female, and embryo genotypes [ 6 ], although genetic or permanent environmental factors are of low importance due to the high variability in litter size [ 7 ]. The success of selection for high prolificacy may be due largely to an increase in the number of corpora lutea [ 8 , 9 ], with associated negative consequences for the resulting foetal-placental units [ 9 11 ]. Indeed, in pigs, it has been shown that selection for increased litter size leads to a significantly lower mean birth weight and a greater percentage of small piglets born [ 12 , 13 ], with the possibility of various degrees of intrauterine growth retardation occurring in these small piglets [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In polytocous livestock species, litter size is studied in order to increase prolificacy, which is the result of complex interactions between male, female, and embryo genotypes [ 6 ], although genetic or permanent environmental factors are of low importance due to the high variability in litter size [ 7 ]. The success of selection for high prolificacy may be due largely to an increase in the number of corpora lutea [ 8 , 9 ], with associated negative consequences for the resulting foetal-placental units [ 9 11 ]. Indeed, in pigs, it has been shown that selection for increased litter size leads to a significantly lower mean birth weight and a greater percentage of small piglets born [ 12 , 13 ], with the possibility of various degrees of intrauterine growth retardation occurring in these small piglets [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…feed efficiency and homogeneity and robustness. Silalahi et al [26] argued that animals selected for high production efficiency might be more susceptible to behavioral, physiological, or immunological problems, thus making them less robust [2729].…”
Section: Discussionmentioning
confidence: 99%
“…L'estimation des évolutions génétiques à partir de semence congelée leur est tout à fait complémentaire, dans la mesure où elle est non limitée en termes de caractères mesurés et ne dépend pas du modèle utilisé pour l'évaluation. De fait, la semence congelée des verrats nés en 1977, évoqués ci-dessus, a été à nouveau utilisée au début des années 2000 pour estimer les évolutions génétiques sur la période 1977-1998 pour un grand nombre de caractères mesurés sur le porc en croissance dans les races LW et LR (Bazin et al, 2003), complétée en race LW par des estimations pour les caractères de reproduction, de comportement (Canario et al, 2007a ;Tribout et al, 2010 ;Canario et al, 2014 ;Silalahi et al, 2016 ;2017).…”
Section: Contrôle De L'efficacité Des Programmes Et éValuation Des (Combinaisons De) Types Génétiquesunclassified
“…Les valeurs initiales pour chaque race sont fixées arbitrairement pour permettre de différencier les courbes. Silalahi et al (2016). Elles le sont moins avec les estimations de Molénat et al (1986) et d'Ollivier et al (1991 mais, comme le discutent Ollivier et al (1991), ces dernières sont vraisemblablement surestimées.…”
unclassified